The method of exploring racism in Zootopia (2016) - Rafly Pratama Putra; Aris Wuryantoro; Vita Vendityaningtyas (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2022)
This research attempts to find out kind of racism and the method used to explore racism in Zootopia Movie. This research is conducted in order to answer the research questions, “How does Zootopia Movie exploring racism?”, and to analyze the method of exploring racism in Zootopia Movie. The subject of this research movie entitled Zootopia (2016) produced by Disney, directed by Byron Howard and Rich Moore. The researcher using qualitative method for the research. The data are collected from the movie Zootopia as a primary data and related journals as a secondary data by using Documentation technique. The researcher using sampling technique and content analysis technique to analyze data. The result of analysis the data confirmed that Disney use transportation imagery model, representation, theory of mind, and reception to explore racism in Zootopia Movie that are applied from the beginning of the movie to the middle of the movie, Zootopia Movie manages to convey the message quite well, this is proven by the response from the Zootopia Movie audience who understands the content of the message.